Stainless steel accelerated thermal aging experiment method based on energy analysis

Through the accelerated thermal aging experimental method of stainless steel based on energy analysis, using differential thermal analysis method and Arrhenius' law, the problem of the existing technology being difficult to quickly evaluate the thermal aging damage of stainless steel materials is solved, and the rapid and quantitative evaluation and prediction of material properties are achieved. Provides support for the safety and stability of nuclear power reactors.

CN119438306AActive Publication Date: 2025-02-14YANGJIANG NUCLEAR POWER +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411670786.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and quantitatively evaluate and predict thermal aging damage of stainless steel materials under long-term high-temperature service conditions, resulting in increased risk of material performance deterioration and brittle fracture of components, and it is difficult to meet the safety and stability requirements of nuclear power reactors.

Method used

The accelerated thermal aging experimental method of stainless steel based on energy analysis is adopted to obtain the heat flow-temperature curve of stainless steel by differential thermal analysis method, and the integrated processing is carried out after correction to obtain characteristic enthalpy, calculate the thermal aging activation energy, and calculate the accelerated thermal aging time by using Arrhenius's law. , test material impact work to evaluate thermal aging damage.

Benefits of technology

The rapid, quantitative assessment and prediction of thermal aging damage of stainless steel materials is achieved, providing strong support for material reliability and safety, and reducing the risk of brittle fracture of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438306A_ABST
    Figure CN119438306A_ABST
Patent Text Reader

Abstract

The invention discloses a stainless steel accelerated thermal aging experiment method based on energy analysis. The method comprises the steps that S1, a heat flow-temperature curve of original state stainless steel and a heat flow-temperature curve of thermal aging stainless steel are obtained; s2, obtaining a corrected heat flow-temperature curve of the stainless steel according to the two heat flow-temperature curves, and obtaining a characteristic peak of the thermally aged stainless steel; s3, carrying out integration processing on the characteristic peak and taking an absolute value to obtain a characteristic enthalpy; s4, thermal aging activation energy Q of the stainless steel material is obtained through calculation according to the characteristic enthalpy; s5, calculating to obtain the thermal aging time required for reaching the same thermal aging damage degree at the accelerated thermal aging temperature; and S6, after the stainless steel material is subjected to accelerated thermal aging at the accelerated thermal aging temperature higher than the actual service temperature, the impact energy of the stainless steel material after service at the actual service temperature is obtained. According to the method, the performance of the stainless steel subjected to thermal aging damage can be rapidly and quantitatively evaluated and predicted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material aging detection, and in particular to a stainless steel accelerated thermal aging experimental method based on energy analysis. Background Art

[0002] Ferrite-containing stainless steel materials have been widely used in many fields such as nuclear power and petrochemicals due to their excellent strength, corrosion resistance and oxidation resistance. Ferrite-containing stainless steel materials, especially Z3CN20.09M / CF3 / CF8 duplex stainless steel containing ferrite, are widely used in key components such as nuclear power primary circuit main pipelines, main coolant pump casings and key valves. In addition, ferrite alloys with FeCrAl as the main component are considered to be the forefront of the research and development of advanced nuclear fuel cladding materials (ATF) due to their excellent oxidation resistance. Ferrite-martensitic stainless steel, with its advantages in strength and radiation resistance, has been selected as the first choice for key structural materials of fourth-generation nuclear power reactors and fusion reactors. The reliability and safety of these materials are crucial to the safe and stable operation of nuclear reactors.

[0003] Although the above-mentioned ferrite-containing stainless steel exhibits excellent performance under complex working conditions, it will suffer significant thermal aging damage when in service for a long time in the temperature range of 300℃-500℃. From a microscopic perspective, the damage is mainly caused by the presence of Cr-rich α' phase and Ni- and Si-rich G phase in ferrite, which leads to significant degradation of the macroscopic mechanical properties of the material, specifically manifested as increased hardness and brittleness of the material, and decreased toughness and impact properties. These performance reductions increase the risk of brittle fracture of components, thus posing a threat to the safety and stability of nuclear power reactors.

[0004] Existing preparation technologies can ensure that the initial state of the material meets the standard performance requirements. However, under long-term high-temperature service conditions, whether the material can operate reliably during its life cycle and the degree of performance degradation have always been important issues of concern to the engineering community. At present, the aging assessment of stainless steel materials usually relies on full-scale impact and fracture toughness tests on thermally aged materials, which requires a large number of destructive experiments and results in a large amount of material loss. The experiment takes several years, which is too long and expensive to meet the current requirements of material damage assessment and new material development. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a stainless steel accelerated thermal aging test method based on energy analysis.

[0006] The technical solution adopted by the present invention to solve the technical problem is: to provide a stainless steel accelerated thermal aging test method based on energy analysis, comprising the following steps:

[0007] S1. Using a differential thermal analysis method to obtain a heat flow-temperature curve of original stainless steel and a heat flow-temperature curve of heat-aged stainless steel;

[0008] S2. Obtaining a corrected heat flow-temperature curve of the stainless steel according to the two heat flow-temperature curves, and obtaining characteristic peaks of the heat-aged stainless steel;

[0009] S3, integrating the characteristic peak in the corrected heat flow-temperature curve of the stainless steel and taking the absolute value to obtain the characteristic enthalpy H;

[0010] S4. Substituting the characteristic enthalpy H into formula (1), calculating the activation energy Q of thermal aging of the stainless steel material;

[0011]

[0012] Among them, a and b are the fitting coefficients obtained after the thermal aging test of stainless steel materials;

[0013] S5. Based on the Arrhenius law, the actual service temperature T1 and service time t1 of the stainless steel material and the proposed accelerated heat aging temperature T2 are substituted into formula (II) to calculate the heat aging time t2 required to achieve the same degree of heat aging damage at the accelerated heat aging temperature T2;

[0014]

[0015] Among them, Q is the thermal aging activation energy of stainless steel material, and R is the molar gas constant;

[0016] S6. After subjecting the stainless steel material to accelerated thermal aging for t2 under conditions of an accelerated thermal aging temperature T2 higher than the actual service temperature T1, the impact energy of the stainless steel material is tested to obtain the impact energy of the stainless steel material after serving for t1 hours at the actual service temperature T1.

[0017] Preferably, in step S4, based on the experimental results of stainless steel material with a chromium content between 10wt.% and 40wt.% and a ferrite content between 15wt.% and 25wt.% under thermal aging at 400°C for 6000h, coefficients a=21.3 and b=42.6 are fitted.

[0018] Preferably, in step S1, the heat flow-temperature curve of the original stainless steel is obtained by the following operation:

[0019] After removing the oxide layer on the surface of the original stainless steel, sampling is performed and measured using a differential thermal analysis method to obtain a heat flow-temperature curve of the original stainless steel;

[0020] The heat flow-temperature curve of heat-aged stainless steel is obtained by the following operation:

[0021] The original stainless steel is subjected to high-temperature thermal failure treatment, and after the surface oxide layer is removed, samples are taken and measured using the differential thermal analysis method to obtain the heat flow-temperature curve of the thermally aged stainless steel.

[0022] Preferably, in step S2, the heat flow-temperature curve of the heat-aged stainless steel is deducted from the heat flow-temperature curve of the original stainless steel, and the baseline is deducted, so as to obtain a corrected heat flow-temperature curve of the stainless steel.

[0023] Preferably, in step S1, the temperature range of the differential thermal analysis method is 300°C to 800°C, and the heating rate is 7°C / s to 15°C / s.

[0024] Preferably, the stainless steel includes Z3CN20.09M stainless steel, CF3, CF8, CF8M, and 2205 duplex stainless steel alloy.

[0025] The beneficial effects of the present invention are as follows: by combining the heat flow-temperature curve obtained by differential thermal analysis, the activation energy and the Arrhenius law, the performance of stainless steel after thermal aging damage can be quickly and quantitatively evaluated and predicted, providing strong support for the reliability and safety of materials in the nuclear power field. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:

[0027] Figure 1 is a heat flow-temperature curve diagram of the original stainless steel in the present invention;

[0028] Figure 2 is a heat flow-temperature curve diagram of the heat-aged stainless steel of the present invention;

[0029] Figure 3 The present invention is based on Figure 1 and Figure 2 The corrected HT curve obtained. DETAILED DESCRIPTION

[0030] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.

[0031] The stainless steel accelerated thermal aging test method based on energy analysis of the present invention may include the following steps:

[0032] S1. The heat flow-temperature curve of the original stainless steel and the heat flow-temperature curve of the heat-aged stainless steel are obtained by differential thermal analysis.

[0033] Specifically, the heat flow-temperature curve of the original stainless steel is obtained by the following operation: after removing the surface oxide layer of the original stainless steel, sampling is performed and the heat flow-temperature curve of the original stainless steel is obtained by measuring using a differential thermal analysis method.

[0034] The heat flow-temperature curve of heat-aged stainless steel is obtained by the following operation: the original stainless steel is subjected to high-temperature thermal failure treatment, and after removing the surface oxide layer, a sample is taken and the heat flow-temperature curve of the heat-aged stainless steel is obtained by measuring using a differential thermal analysis method.

[0035] In the differential thermal analysis method, the temperature range is 300°C to 800°C, and the heating rate is 7°C / s to 15°C / s.

[0036] S2. Obtain a corrected heat flow-temperature curve of the stainless steel based on the two heat flow-temperature curves, and obtain characteristic peaks of the heat-aged stainless steel.

[0037] Specifically, the heat flow-temperature curve of the heat-aged stainless steel is deducted from the heat flow-temperature curve of the original stainless steel, and the baseline is deducted to obtain the corrected heat flow-temperature curve of the stainless steel.

[0038] S3. Integrate the characteristic peak in the corrected heat flow-temperature curve and take the absolute value to obtain the characteristic enthalpy H.

[0039] S4. Substitute the characteristic enthalpy H into formula (1) to calculate the thermal aging activation energy Q of the stainless steel material;

[0040]

[0041] Among them, a and b are the fitting coefficients obtained after the thermal aging test of stainless steel material.

[0042] In some embodiments, based on the experimental results of stainless steel material with a chromium content between 10wt.% and 40wt.% and a ferrite content between 15wt.% and 25wt.% under 400°C heat aging for 6000h, the coefficients a=21.3 and b=42.6 are fitted.

[0043] It can be understood that the fitting coefficients a and b are different according to different content ranges of chromium, ferrite, etc. and different thermal failure conditions.

[0044] S5. Based on the Arrhenius law, the actual service temperature T1 and service time t1 of the stainless steel material and the proposed accelerated heat aging temperature T2 are substituted into formula (II) to calculate the heat aging time t2 required to achieve the same degree of heat aging damage at the accelerated heat aging temperature T2;

[0045]

[0046] Among them, Q is the thermal aging activation energy of stainless steel material, and R is the molar gas constant.

[0047] S6. After accelerated thermal aging for t2 at an accelerated thermal aging temperature T2 higher than the actual service temperature T1, the impact energy of the stainless steel material is tested to obtain the impact energy of the stainless steel material after serving for t1 hours at the actual service temperature T1.

[0048] The stainless steel applicable to the present invention includes but is not limited to Z3CN20.09M stainless steel, CF3, CF8, CF8M, 2205 duplex stainless steel alloy, etc.

[0049] The present invention is further described below by taking Z3CN20.09M stainless steel as an example.

[0050] The specific steps of the accelerated thermal aging experiment of Z3CN20.09M stainless steel are as follows:

[0051] (1) Remove the surface oxide layer of the original material (i.e., the original Z3CN20.09M stainless steel), take a sample and make a thin slice with a thickness of 80 μm, cut a 5 mg slice sample, and use the differential thermal analysis method to measure the heat flow-temperature curve of the original stainless steel, which is defined as the original HT curve, such as Figure 1 shown.

[0052] (2) The original material is placed in a heat treatment furnace for 3000 hours of heat aging treatment at 400°C to remove the surface oxide layer. The sample is made into a thin slice with a thickness of 80 μm. A 5 mg sheet sample is cut and the heat flow-temperature curve of the heat-aged stainless steel is measured by differential thermal analysis, which is defined as the heat aging HT curve, such as Figure 2 shown.

[0053] (3) Subtract the original HT curve from the thermal aging HT curve and the baseline to obtain the modified HT curve (such as Figure 3 As shown), the characteristic peak of the modified HT curve is integrated and the absolute value is taken to obtain the characteristic enthalpy H=3.64.

[0054] (4) Substituting the characteristic enthalpy H into formula (1) and converting it, we can obtain the thermal aging activation energy of stainless steel material Q = 102.58:

[0055]

[0056] Among them, based on the experimental results of stainless steel materials with a large amount of chromium content between 10wt.% and 40wt.% and a ferrite content between 15% and 25% under 400°C heat aging for 6000 hours, the fitting coefficients a=21.3 and b=42.6 were obtained.

[0057] (5) Based on the Arrhenius law, the actual service temperature (T1 = 300 °C) and service time (40 years, t1 = 350400 h) of the stainless steel material and the proposed accelerated thermal aging temperature (T2 = 400 °C) are substituted into formula (II):

[0058]

[0059] Among them, the actual service temperature T1 = 300°C, the aging time t1 = 350400h, Q = 102.58kJ / mol, R = 8.314J / mol / K, and the calculated thermal aging time t2 = 14292h required to reach the same degree of thermal aging damage at this temperature (T2 = 400°C).

[0060] (6) After the stainless steel material was subjected to accelerated thermal aging for 14292 hours at an accelerated thermal aging temperature of 400°C, which is higher than the actual service temperature, the impact energy of the stainless steel material was tested (109±16.8J). The impact energy of the stainless steel material after serving for 350400 hours (about 40 years) at the actual service temperature of 300°C was obtained to be 107±18.2J.

[0061] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A stainless steel accelerated thermal aging test method based on energy analysis, characterized in that: The following steps are involved: S1. Using a differential thermal analysis method to obtain a heat flow-temperature curve of original stainless steel and a heat flow-temperature curve of heat-aged stainless steel; S2. Obtaining a corrected heat flow-temperature curve of the stainless steel according to the two heat flow-temperature curves, and obtaining characteristic peaks of the heat-aged stainless steel; S3, integrating the characteristic peak in the corrected heat flow-temperature curve of the stainless steel and taking the absolute value to obtain the characteristic enthalpy H; S4. Substituting the characteristic enthalpy H into formula (1), calculating the activation energy Q of thermal aging of the stainless steel material; Among them, a and b are the fitting coefficients obtained after the thermal aging test of stainless steel materials; S5. Based on the Arrhenius law, the actual service temperature T1 and service time t1 of the stainless steel material and the proposed accelerated heat aging temperature T2 are substituted into formula (II) to calculate the heat aging time t2 required to achieve the same degree of heat aging damage at the accelerated heat aging temperature T2; Among them, Q is the thermal aging activation energy of stainless steel material, and R is the molar gas constant; S6. After subjecting the stainless steel material to accelerated thermal aging for t2 under conditions of an accelerated thermal aging temperature T2 higher than the actual service temperature T1, the impact energy of the stainless steel material is tested to obtain the impact energy of the stainless steel material after serving for t1 hours at the actual service temperature T1.

2. The accelerated thermal aging test method for stainless steel based on energy analysis according to claim 1, characterized in that: In step S4, based on the experimental results of stainless steel material with a chromium content between 10wt.% and 40wt.% and a ferrite content between 15wt.% and 25wt.% under heat aging at 400°C for 6000h, coefficients a=21.3 and b=42.6 are fitted.

3. The accelerated thermal aging test method for stainless steel based on energy analysis according to claim 1, characterized in that: In step S1, the heat flow-temperature curve of the original stainless steel is obtained by the following operation: After removing the oxide layer on the surface of the original stainless steel, sampling is performed and measured using a differential thermal analysis method to obtain a heat flow-temperature curve of the original stainless steel; The heat flow-temperature curve of heat-aged stainless steel is obtained by the following operation: The original stainless steel is subjected to high-temperature thermal failure treatment, and after the surface oxide layer is removed, samples are taken and measured using the differential thermal analysis method to obtain the heat flow-temperature curve of the thermally aged stainless steel.

4. The accelerated thermal aging test method for stainless steel based on energy analysis according to claim 1, characterized in that: In step S2, the heat flow-temperature curve of the heat-aged stainless steel is deducted from the heat flow-temperature curve of the original stainless steel, and the baseline is deducted to obtain a corrected heat flow-temperature curve of the stainless steel.

5. The accelerated thermal aging test method for stainless steel based on energy analysis according to claim 1, characterized in that: In step S1, the temperature range of the differential thermal analysis method is 300°C to 800°C, and the heating rate is 7°C / s to 15°C / s.

6. The accelerated thermal aging test method for stainless steel based on energy analysis according to any one of claims 1 to 5, characterized in that: The stainless steel includes Z3CN20.09M stainless steel, CF3, CF8, CF8M, and 2205 duplex stainless steel alloy.

Citation Information

Patent Citations

  • Method for evaluating thermal ageing state of duplex stainless steel by use of thermoelectric potential

    CN104181096A

  • Rapid evaluation method for thermal safety of small-dose explosive based on adiabatic accelerated calorimetry

    CN116206705A

  • Method of assessing the lifetime of structures and the system for assessing the same

    KR102241620B1

  • Composite graphite material and preparation method therefor, negative electrode plate, secondary battery, battery module, battery pack, and powered device

    WO2023040319A1